1989
DOI: 10.1089/jir.1989.9.373
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Group of Interferons Associated with the Early Ovine and Bovine Embryo

Abstract: Recently, two proteins, ovine trophoblast protein-1 (oTP-1) and bovine trophoblast protein-1 (bTP-1), that are major products of the preimplantation ovine and bovine embryo, respectively, have been shown to be interferons (IFNs). Both proteins belong to an IFN-a subfamily whose polypeptide chains are 172 amino acids long. oTP-1 and bTP-1 have been strongly implicated in triggering maternal responses to the presence of a viable embryo and in maintaining pregnancy. Thus, a new and totally unsuspected role for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…The levels of activity in the present study were higher than reported by Cross & Roberts (1989 (Cross & Roberts, 1989 (Roberts, 1989), pig interferon activity seems to appear and to peak on about the same days. In sheep, oTP-1 synthesis followed by quantifying specific mRNA from conceptuses in culture (Farin et ai, 1989) (Geisert et ai, 1982b).…”
Section: Discussioncontrasting
confidence: 80%
“…The levels of activity in the present study were higher than reported by Cross & Roberts (1989 (Cross & Roberts, 1989 (Roberts, 1989), pig interferon activity seems to appear and to peak on about the same days. In sheep, oTP-1 synthesis followed by quantifying specific mRNA from conceptuses in culture (Farin et ai, 1989) (Geisert et ai, 1982b).…”
Section: Discussioncontrasting
confidence: 80%
“…lA). The aspect 24-h postinfection revealed two main characteristics: (1) a complete collapse of blastocysts, except those that were not hatched; and (2) a gross damage of L 929 cells as shown by the appearance of giant cells corresponding to syncitia. The as- (Table I).…”
Section: Solid Phase Elisamentioning
confidence: 99%
“…In several animal species, interferons (lFNs) are found to be secreted by the embryonic trophoblast at the time of implantation. 1 In ruminants, embryonic IFNs related to type I IFN, identical to the known trophoblast protein-l (TP I) or trophoblastins, playa role in the maternal recognition of pregnancy, by maintaining the corpus luteum (CL) functions. [2][3][4] Recent results indicate that equine embryos might also secrete TPI-like IFN.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have been published on various aspects of this topic (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). This discovery attracted considerable attention because it revealed a new and completely unsuspected role for a cytokine as a reproductive hormone.…”
mentioning
confidence: 99%